1998
DOI: 10.1038/bjc.1998.711
|View full text |Cite
|
Sign up to set email alerts
|

Do patients with advanced breast cancer benefit from chemotherapy?

Abstract: Summary This study aimed to assess the proportion of patients with advanced breast cancer who report benefit from first-line palliative chemotherapy using a simple global measure of wellbeing and to identify factors predicting benefit. A consecutive series of women with advanced breast cancer undergoing first-line palliative chemotherapy was evaluated. The main outcome measure was patient report of overall wellbeing assessed at post-treatment interview. Physical, psychological and functional status were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 16 publications
1
20
0
2
Order By: Relevance
“…An objective response to chemotherapy (measured as a reduction in tumour bulk) is associated with improvement in both symptoms and performance status (Baum et al, 1980;Ramirez et al, 1998;Geels et al, 2000) and therefore clinicians would perceive these 2 goals as achievable. This study did not examine the influence of individual chemotherapeutic drugs on evaluations of the goals of palliative chemotherapy.…”
Section: The Goals Of Palliative Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…An objective response to chemotherapy (measured as a reduction in tumour bulk) is associated with improvement in both symptoms and performance status (Baum et al, 1980;Ramirez et al, 1998;Geels et al, 2000) and therefore clinicians would perceive these 2 goals as achievable. This study did not examine the influence of individual chemotherapeutic drugs on evaluations of the goals of palliative chemotherapy.…”
Section: The Goals Of Palliative Chemotherapymentioning
confidence: 99%
“…Initial disease-free interval and abnormal liver function tests/liver metastases have been identified as important prognostic factors (Namer et al, 1990;Falkson et al, 1991;Gregory et al, 1993) but evidence relating to other disease and patient characteristics is conflicting. Preliminary work has been undertaken to identify the factors predicting patient-reported benefit from first-line palliative chemotherapy using a simple global measure of well-being (Ramirez et al, 1998). High levels of psychological distress and the presence of a dry mouth prior to treatment were found to predict feeling worse after treatment.…”
mentioning
confidence: 99%
“…There are studies in which chemotherapy appears to enhance patients' quality of life (Thatcher et al, 1997;Stockler et al, 1998;Tannock, 1998;Geels et al, 2000;Doyle et al, 2001). Ramirez et al (1998) found that only 25% of the patients benefited from chemotherapy in her study, and there are several studies in which no improvement or even deterioration of quality of life was reported (Quantin et al, 2000;van Andel et al, 2000;Barras et al, 2001;Schiller et al, 2001). Values of patients thus become more important.…”
mentioning
confidence: 92%
“…We therefore suggest that because most breast tumor cells with mtp53 fail to respond to first-line chemotherapeutic treatment (43), PRIMA-1 should be investigated as a potential alternative treatment strategy, either alone for tumors expressing high levels of p53, or in combination with anti-hormones, antiangiogenesis based antibodies, chemotherapeutic compounds, or vascular disrupting agents. We believe that such novel therapies may lead to a higher rate of success in the treatment of breast cancer.…”
Section: Discussionmentioning
confidence: 99%